Dispersión del piru (Schinus molle L., Anacardiaceae) por aves en Teotihuacán, México - Corkidi, Lea; Cacho, Sonia; Burquez, Alberto (Instituto de Ecología, A.C., 1991)
The dispersal ecology of the pepper tree (Schinus molle L.), introduced from Perú to México in the sixteenth century, is studied in the surroundings of Teotihuacán, State of México. Only the cedar waxwing (Bombycilla cedrorum) was consistently observed eating its fruits, despite of the presence in the study area, of many of the birds reported as dispersers. Germination  ests show that the seeds eaten by birds, or those in which the  exocarp was removed, germinate faster and have a higher  percentage germination. Fruits passing through the digestive tract of birds lose 8% of their total sugar content. The timing from ingestión to egestion was about 25 min. This interval is more than 50 times longer than the time the birds spend perching in the tree (5T= 27 sec). It is concluded that Bombycilla is one of the most important dispersal agents of Schinus in Teotihuacan. It probably played a major role in the rapid spreadof Schinus molle in the Mexican Central Plateau more than 400 years ago. The importance of this tree for ecological and evolutionary studies is discussed as the dates of introduction to different places in the world are documented.